Encouraging the Shift of Modes of Freight Transport from Road to Railways in Indonesia (Case Study: Java Island) - Sugesti, Bagus Gesit; Priyanto, Sigit; Irawan, Muhammad Zudhy; Whiteing, Anthony (Universitas Ibn Khaldun Bogor, 2024)
Freight transportation has a positive effect on the development, on the other hand, transportation also has negative impacts that need to be considered. Rail as a mode that has the potential to be a solution is still little used compared to trucks. This research aims to investigate the weighting factors and actors in Indonesia to encourage the shift of freight transport modes from trucks to railways, to know the constrain the utilization of railways as a mode of freight transportation and provide policy recommendations by benchmarking from other countries. The research was carried out using qualitative and quantitative methodologies. A qualitative approach was carried out through a literature review covering various countries and sources, and interviews with experts. The analytic hierarchy process is formulated for quantitative analysis and executed with Expert Choice software. Data was collected through a questionnaire, with a purposive sampling method. The results show that Time, Service Quality and Area Coverage are considered as the 3 main factors with the highest weight. Government and Logistics Service Providers are the most influential actors in promoting the shift of freight from trucks to trains. Recommendations for priority policies are policies related to factors and involving actors with the greatest weight, and overcoming the obstacles that exist in Indonesia in using trains as a mode of freight transportation by increasing modal transfer facilities to increase the efficiency of freight transportation via train, with support from the government in the form of incentives as has been done by the Britain Railway.